The Essence of the Concept of Diversion in General Criminal Offenses - Asmara, I Dewa Gede Budhy Dharma (Journal of Legal and Cultural Analytics, 2025)
The handling of general criminal cases with a sentence of less than five years, provided they are not repeat offenses, is increasingly being directed toward a diversion mechanism based on the principles of restorative justice. This approach aims to restore relationships between the offender, the victim, and the community through dialogue and mediation, rather than focusing on punishment. Restorative justice emphasizes the offender’s responsibility toward the victim and the community, with the primary goal of fostering social harmony and avoiding the negative impacts of conventional sentencing. In Indonesia, restorative justice has been recognized in various regulations, such as Law Number 11 of 2012 on the Juvenile Criminal Justice System and Supreme Court Regulation Number 4 of 2014, which highlights the importance of diversion as a means of resolving criminal cases outside of court proceedings. Additionally, Prosecutor’s Decree Number 15 of 2020 allows for the discontinuation of prosecution in minor cases under certain conditions. The concept of restorative justice, introduced by Albert Eglash in 1977, distinguishes three forms of justice: retributive, distributive, and restorative. This principle of restoration has long been recognized in various legal traditions, including in Indonesia, where customary law (living law) plays a significant role. By prioritizing mediation and restitution, restorative justice offers a new paradigm in the criminal justice system—one that is more humane and focused on social recovery.